Nonthermally driven volatilome evolution of food matrices: The case of high pressure processing. (December 2020) - Xia, Qiang; Zheng, Yuanrong; Liu, Zhenmin; Cao, Jinxuan; Chen, Xiaojia; Liu, Lianliang; Yu, Huaning; Barba, Francisco J.; Pan, Daodong
Abstract: Background: The adoption of innovative nonthermal processing as alternatives to conventional heating techniques in the food industry is mainly relied on their tremendous potential to simultaneously achieve preservation purposes and the maintenance of fresh-like characteristics and health benefits of final products. With increasing evaluation for the applicability of nonthermal processing, there remains, however, a great challenge for keeping the balance between the efficiency of microbial/enzymatic inactivation and the maintenance of sensory and nutritional characteristics. Accordingly, a timely summarization and elucidation of the response pattern and mechanism of related quality parameters under nonthermal conditions is of great importance. Scope and approach: In this review, the nonthermal effects of high pressure processing (HPP) on volatilome evolution are discussed, considering its close relationship with food flavor quality. It starts with elucidating the pressurization principles linked to volatilome evolution. Then, the general volatile fingerprinting features responding to HPP in major food items are summarized, followed by the analysis of the response mechanisms behind. Finally, the potential of innovative applications based on HPP-induced volatilome evolution is discussed. Key findings and conclusions: A critical examination of newly updated findings has suggested the non-negligible spatiotemporal HPP effects on the headspace volatile fingerprinting and flavor perception of pressurized foods. HPP-induced volatilome evolution results from the biochemical, physical, and chemical as well as metabolic effects of high pressure, and specific mechanisms depend on the features and manufacturing crafts of sample matrices, process variables and processing patterns. HPP shows its great potential as an aroma modification and flavor-tailoring technique, based on a comprehensive understanding of the mechanistic and quantitative relationship between volatilome evolution and process parameters. Graphical abstract: Image 1 Highlights: Volatile fingerprint features of major pressurized food are summarized and updated. The principles of high-pressure (HP) effects on volatilome evolution are described. Nonthermal effects during pressurization greatly promote volatilome evolution. Response of food volatilome to HP treatments is a complex multi-factor function. HP processing can be used as an aroma modification and flavor-tailoring technique.